Surgical stress biomarkers as early predictors of postoperative infectious complications in patients with colorectal cancer - Liu, Jing-Jing; Yang, Ming-Shi; Cen, Chao-Qun; Xu, Chun; Yuan, Hong (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: The aim of this study was to determine if the serum surgical stress biomarkers tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10) could predict infectious complications in patients who underwent colorectal cancer (CRC) surgery. Methods: A total of 200 consecutive patients who underwent resection for primary CRC were enrolled. The clinicopathological characteristics, serum TNF-α and IL-10 levels, and infectious complications were analyzed. The TNF-α and IL-10 levels were classified using cut-off values based on a ROC analysis. Results: Infectious complications developed in 27 (13.5%) patients. Patients with complications had higher serum IL-10 levels than those without complications during the first 5 postoperative days (PODs) (P35.3 ng/L on POD 3 or >20.3 ng/L on POD 5 was associated with the occurrence of infectious complications (all P6.9 ng/L and a TNF-α level >8.1 ng/L on POD 1 and >7.5 ng/L on POD 3 were confirmed as sensitive and specific predictors of complications (P